O conto sob a perspectiva da psicolinguística em interface com a literatura : compreensão leitora, consciência textual e processamento - Prado, Leandro Lemes do (2018)
Psycholinguistics has devoted itself to studying the connections between language and mind, so that its space between studies on language is allocated to cognition, specifically as it relates to the processing of reading comprehension and textual consciousness. The reading difficulties of Elementary and High School students have been a constant concern for all educational professionals who are in charge of finding teaching methods that allow to solve this problem in the diverse textual genres. In view of these considerations, this thesis chooses the literary text, specifically the short story, as the central working text, since this genre is frequent and relevant in the school environment. In this section, Literature is defined as the interface of Psycholinguistics. In order to construct a linguistic-literary paradigm favorable to the progress of the studies on the reading comprehension, its processing and the textual conscience in the reading of the story, instruments were developed that were applied in three distinct groups of readers. The obtained data were analyzed and discussed. As a result, it was verified in the participants' performance that the superstructure is the macroposition of the short-story in which there were the smallest hit scores, and in grammatical cohesion the best hit scores. The performances were still better at understanding than at knowledge. In processing, there was a tendency to personal opinion. It can be seen from the results that, in the textual awareness of the story, a search for the full development of his knowledge is necessary. Based on data and discussions, the research aims to contribute to the teaching of reading, so that it is possible to be guided by the presence of literary textual genres, in order to qualify the teaching and learning process as a whole.